2010
DOI: 10.1681/asn.2010040409
|View full text |Cite
|
Sign up to set email alerts
|

Adenylate Cyclase 6 Determines cAMP Formation and Aquaporin-2 Phosphorylation and Trafficking in Inner Medulla

Abstract: Arginine vasopressin (AVP) enhances water reabsorption in the renal collecting duct by vasopressin V 2 receptor (V 2 R)-mediated activation of adenylyl cyclase (AC), cAMP-promoted phosphorylation of aquaporin-2 (AQP2), and increased abundance of AQP2 on the apical membrane. Multiple isoforms of adenylate cyclase exist, and the roles of individual AC isoforms in water homeostasis are not well understood. Here, we found that levels of AC6 mRNA, the most highly expressed AC isoform in the inner medulla, inversely… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
90
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 85 publications
(99 citation statements)
references
References 49 publications
(68 reference statements)
6
90
1
Order By: Relevance
“…Because the actin barrier forms in the absence of vasopressin stimulation (13,33), we overhydrated the animals to block vasopressin release. Animals were water-loaded by oral gavage (3% total body weight) as described previously (38). Kidneys were harvested 90 min after water loading and fixed in formalin.…”
Section: Resultsmentioning
confidence: 99%
“…Because the actin barrier forms in the absence of vasopressin stimulation (13,33), we overhydrated the animals to block vasopressin release. Animals were water-loaded by oral gavage (3% total body weight) as described previously (38). Kidneys were harvested 90 min after water loading and fixed in formalin.…”
Section: Resultsmentioning
confidence: 99%
“…We found that the EX4-induced and GLP-1R-mediated natriuresis and NHE3 phosphorylation in the mouse are not associated with an increase in urinary cAMP excretion and persisted in AC6-deficient mice. AC6 is the most abundant AC isoform in rat whole kidney (36) and mouse medulla (33) on the basis of mRNA expression and the dominant AC isoform with regard to forskolin-induced cAMP formation in mouse kidney (4) and inner medulla (33). It could be that the impact of proximal tubule release on total urinary cAMP excretion is lower in mice than rats, although application of parathyroid hormone, which is thought to activate proximal tubular AC, increased urinary cAMP-to-creatinine ratios threefold in mice (43), a finding confirmed in the present studies.…”
Section: Discussionmentioning
confidence: 99%
“…Mice were randomized to application of EX4 (10 g/kg ip; Sigma-Aldrich, St. Louis, MO), ALG (10 mg/kg ip; Takeda Pharmaceuticals, Oak Grove, IL), or vehicle (0.85% NaCl, 2 l/g body wt ip). After their bladders were emptied, the mice were NaCl-loaded by oral gavage (0.85% NaCl, 30 l/g body wt, ϳ30% of daily NaCl intake) and placed in metabolic cages for quantitative urine collection over 3 h without access to food or water (32,33); then blood glucose was measured by tail snip.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations